2020
DOI: 10.18311/mvpjms/2019/v6i2/22994
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Non Neoplastic Skin Diseases: A Histopathology Based Clinicopathological Correlation Study at a Tertiary Health Care Centre

Abstract: Introduction: Skin biopsy probably is the most important ancillary aid to confirm clinical diagnosis. The interpretation of many skin biopsies requires the identification and integration of two different morphological features -the tissue reaction pattern and the pattern of inflammation. Aim: To correlate histopathological diagnosis with clinical diagnosis in various non neoplastic skin lesions. Materials and Methods: The present study was a prospective and observational type of study. A total number of 197 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In another case, a diagnosis of lichen planus pigmentosus was given clinically diagnosed as eruptive lichen planus. In about 25% of the cases, the clinical 5,7,9 In this study maximum clinical lesions presented as plaque like lesions, similar to finding by study of Bajaj et al 7 In this study, with respect to duration of illnesses, 39.16% of cases presented with a duration of 1-6 months in agreement with the study of Vaghela et al where also, most cases (44%) presented within 0-6 months. 10 In this study authors observed that maximum number of cases i.e.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In another case, a diagnosis of lichen planus pigmentosus was given clinically diagnosed as eruptive lichen planus. In about 25% of the cases, the clinical 5,7,9 In this study maximum clinical lesions presented as plaque like lesions, similar to finding by study of Bajaj et al 7 In this study, with respect to duration of illnesses, 39.16% of cases presented with a duration of 1-6 months in agreement with the study of Vaghela et al where also, most cases (44%) presented within 0-6 months. 10 In this study authors observed that maximum number of cases i.e.…”
Section: Resultssupporting
confidence: 91%
“…5 Vesicobullous lesions were less common in our study with 5 (4.16%) reported cases. Leprosy was also the most common lesion in studies by Bajaj et al, Narang et al, D Costa et al(Study in pediatric population) and Rohit et al 2,7,9 In another study also conducted in western UP over a 4 year period by Grover et al, inflammatory diseases (Bullous lesions and Psoriasis) was the most common group (73.47% cases) while infectious diseases was the second most common group (22.99% cases), leprosy being the most common. 13 In this study, leprosy comprised 87.7% of the infectious lesions, this percentage was 78.26% in study by Rohit et al 2 In, a study of Non neoplastic skin lesions by Vaghela et al in Gujarat, most common lesion was observed to be inflammatory disease of the dermis and epidermis (51%), while infectious diseases of skin (25%) was the second most common.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation